Pemodelan dan simulasi antrian kendaraan di gerbang tol - Sediono, Wahju; Handoko, Dwi (2004)
The traffic situations in Indonesian big cities, especially in the capital city, are so crowded that traffic jam can be found anywhere at anytime. This traffic condition may causes several problems such noise problem, environmental problem, energy loss problem and others. Even it is easy to understand if this undesirable conditions could give the influence on the national productivity at all levels of society. In order to decrease such traffic jam problems, a well planned traffic rules may usefully to reduce the traffic jam. Currently, we are developing traffic simulation tools in BPPT, in order to be applied in the traffic planning. In this paper a model of traffic conditions at the highway gate driven by the vehicles in- and outflow is introduced. This modeling is so flexible that it can also be used to model various queuing systems such as queues at the cashiers of supermarket and in the bank. By using this model we can also perform simple traffic analyses in the highway gate.